2008
DOI: 10.1002/jcp.21427
|View full text |Cite
|
Sign up to set email alerts
|

The role of viral and bacterial pathogens in gastrointestinal cancer

Abstract: The association of Helicobacter pylori (H. pylori) with gastric cancer is thus far the best understood model to comprehend the causal relationship between a microbial pathogen and cancer in the human gastrointestinal tract. Besides H. pylori, a variety of other pathogens are now being recognized as potential carcinogens in different settings of human cancer. In this context, viral causes of human cancers are central to the issue since these account for 10–20% of cancers worldwide. In the case of H. pylori and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 207 publications
(197 reference statements)
0
41
0
2
Order By: Relevance
“…Specific agents, such as Helicobacter pylori, human papillomavirus, Epstein-Barr virus, and JC virus, have been directly implicated in the etiopathogenesis of several tumors, including gastrointestinal cancers (31,32).…”
Section: Figurementioning
confidence: 99%
“…Specific agents, such as Helicobacter pylori, human papillomavirus, Epstein-Barr virus, and JC virus, have been directly implicated in the etiopathogenesis of several tumors, including gastrointestinal cancers (31,32).…”
Section: Figurementioning
confidence: 99%
“…Concurrently, the intestine must tolerate an extensive load of microbiota and is susceptible to various types of acute and chronic infection that can elicit intestinal inflammation. Not surprisingly, alterations in human microbiota, as well as bacterial infections, mainly due to Helicobacter species, have been inextricably linked to gastrointestinal disease and cancer (2)(3)(4). Yet while bacterial infection has been associated with blood cell infiltration and the induction of immune responses, its role in carcinogenesis has not been demonstrated conclusively (3)(4)(5).…”
mentioning
confidence: 99%
“…Not surprisingly, alterations in human microbiota, as well as bacterial infections, mainly due to Helicobacter species, have been inextricably linked to gastrointestinal disease and cancer (2)(3)(4). Yet while bacterial infection has been associated with blood cell infiltration and the induction of immune responses, its role in carcinogenesis has not been demonstrated conclusively (3)(4)(5). In addition, while the roles of the Notch and K-Ras signaling pathways in human colorectal cancer have been unequivocally demonstrated (6,7), the contribution of these pathways in stem cells (SCs) and progenitors in intestinal tumor initiation remains elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…may have a causal link to gastric carcinogenesis. 38 For example, it is previously reported that Acinetobacter lwoffii infection can induce many of the same histological changes, including atrophy and metaplasia, as gastric Helicobacter infection. 39 In the stomachs of GAS-KO or omeprazole-treated C57BL/6 wild-type mice under conventional housing, chronic gastritis due to bacterial overgrowth was observed and attributed to hypochlorhydria, and then antibiotic treatment successfully resolved the gastric inflammation in these mice.…”
Section: Discussionmentioning
confidence: 99%